Representasi Love Language dalam Video Musik “Sampai Menutup Mata” Versi Mahalini: Analisis Semiotika Ferdinand de Saussure - Febi Febi; Silviana Purwanti; Johantan Alfando WS; Harry Isra Muhammad (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the representation of love language in Mahalini’s Sampai Menutup Mata music video using Ferdinand de Saussure’s semiotic approach. The research employed a qualitative method with semiotic analysis focusing on the relationship between the signifier and the signified in the video’s visual and verbal elements. Data were collected through observation and documentation of the official music video. The findings reveal that love language is represented through various signs, including letters, family photographs, emotional expressions, tears, hugs, physical touch, and song lyrics. Four forms of love language were identified: words of affirmation, acts of service, quality time, and physical touch. Among these, words of affirmation emerged as the dominant representation through letters expressing affection, appreciation, and gratitude. Meanwhile, acts of service, quality time, and physical touch are represented through caring actions, shared family moments, and affectionate physical interactions. The study concludes that the music video portrays love as emotional closeness, appreciation, togetherness, and care within family, romantic, and fan relationships.